"Identifying high throughput path in Wireless Mesh Networks with bandwidth Guarantees (International Journal of Engineering and Computer Science, 2017)
Wireless mesh networks (WMNs) have occurred as a key technology for next generation wireless networking. Because of their advantages over other wireless networks, WMNs are undergoing swift progress and inspiring numerous applications. To accelerate hop-by-hop routing, we develop a mechanism for calculating the available bandwidth of a path in a dispersed manner. Unfortunately, available bandwidth is not isotonic, the obligatory and appropriate property for reliable hop-by-hop routing. To solve the problem, we introduce an isotonic parameter that captures the available bandwidth metric so that packets can traverse the maximum bandwidth path consistently according to the routing tables constructed in the nodes along the path. To the best of our knowledge, our protocol is the first WMN hop-by-hop routing scheme that can identify bandwidth assured paths.